2008
DOI: 10.1128/iai.00446-08
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coliO157:H7 Survives within Human Macrophages: Global Gene Expression Profile and Involvement of the Shiga Toxins

Abstract: Escherichia coli O157:H7 is an important food-borne pathogen that specifically binds to the follicle-associated epithelium in the intestine, which rapidly brings this bacterial pathogen in contact with underlying human macrophages. Very little information is available about the interaction between E. coli O157:H7 and human macrophages. We evaluated the uptake and survival of strain EDL933 during infection of human macrophages. Surprisingly, EDL933 survived and multiplied in human macrophages at 24 h postinfect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
54
6
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 64 publications
7
54
6
1
Order By: Relevance
“…These results were consistent with those of a transcriptional study that used microarray analysis (Poirier et al, 2008). Since genes related to the SOS response in EHEC were upregulated within macrophages (Poirier et al, 2008), Stx2 production in EHEC might be increased within macrophages. However, the mechanism underlying upregulation of Stx1 production in EHEC within macrophages remains unclear.…”
Section: Discussionsupporting
confidence: 89%
“…These results were consistent with those of a transcriptional study that used microarray analysis (Poirier et al, 2008). Since genes related to the SOS response in EHEC were upregulated within macrophages (Poirier et al, 2008), Stx2 production in EHEC might be increased within macrophages. However, the mechanism underlying upregulation of Stx1 production in EHEC within macrophages remains unclear.…”
Section: Discussionsupporting
confidence: 89%
“…A number of pathogenic bacteria have developed a variety of mechanisms to evade host defense mechanisms and enhance their virulence (44). Previous studies showed that Stx or other bacterial factors of STEC, such as EspA, B, and D, downregulate NF-B activation (15,18).…”
Section: Discussionmentioning
confidence: 99%
“…Gb3 synthesis is also induced by cytokines, including tumor necrosis factor (TNF), that are induced by VT2 and lipopolysaccharide (LPS) during infection (8,17). Binding of VT to Gb3 in endothelial cells further increases the expression of Gb3 and exacerbates the disease process by EHEC O157:H7 (16,20). Binding of VT to Gb3 may indirectly promote EHEC O157:H7 adherence, because it represses antibacterial peptide secretion and host cellular immune response (7,23).…”
Section: Discussionmentioning
confidence: 99%